A Case Study to the Tax Arrangements Concerning China’s Biggest Investment Project in Poland - Yusen, Tan (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This paper mainly studies the tax planning arrangements concerning China’s biggest investment project in Poland, a China group’s acquisition of a Poland’s state-owned factory (HSW), and the establishment of a new Polish company to run the newly acquired business obtained from this M&A deal. This paper sheds some light to Chinese investors that intend to invest in the European Union under the newly signed China European Union Agreement on Investment from the perspective of tax planning. The detailed analysis contained in this paper also facilitate tax practitioners and tax authorities in Poland, or even in other EU member states, to deepen their understanding of Chinese investors’ tax motives and concerns relevant to their investment and operation in the EU market. This paper’s academic contribution is summarized as follows: it notices the details omitted by conventional tax planning theories and previous literatures and tries to do an in-depth study to a real Chinese investor’s real behaviors under a real case in order to explain the underlying motives and concerns that determines the Chinese investor’s tax relevant behaviors conducting in such manners.